Genomic analyses provide insights into the genome evolution and environmental adaptation of the tobacco moth Ephestia elutella - Xu, Jiadan; Li, Bo; Jiang, Zhimin; Wang, Weimin; Yang, Yi; Yang, Maofa; Ye, Xinhai (Frontiers in Physiology, 2023)
Ephestia elutella is a major pest responsible for significant damage to stored tobacco over many years. Here, we conduct a comparative genomic analysis on this pest, aiming to explore the genetic bases of environmental adaptation of this species. We find gene families associated with nutrient metabolism, detoxification, antioxidant defense and gustatory receptors are expanded in the E. elutella genome. Detailed phylogenetic analysis of P450 genes further reveals obvious duplications in the CYP3 clan in E. elutella compared to the closely related species, the Indianmeal moth Plodia interpunctella. We also identify 229 rapidly evolving genes and 207 positively selected genes in E. elutella, respectively, and highlight two positively selected heat shock protein 40 (Hsp40) genes. In addition, we find a number of species-specific genes related to diverse biological processes, such as mitochondria biology and development. These findings advance our understanding of the mechanisms underlying processes of environmental adaptation on E. elutella and will enable the development of novel pest management strategies.